2020
DOI: 10.1136/bmj.m1465
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: why we need a national health and social care service

Abstract: Covid-19 outbreaks in care homes expose serious inadequacies in social care services across the UK. Data from across the world show that deaths from covid-19 mainly occur among older people, particularly those over 80. 1 By 12 April 10 612 deaths had been reported in the UK 2-40% of deaths have occurred in those aged 60-79 and 52% in those 80 years or over. 3 Close to 1.5 million vulnerable people are currently self-isolating indoors for 12 weeks. 4 These include many older people and people with disabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 2 publications
(2 reference statements)
0
21
0
5
Order By: Relevance
“…35 An earlier study of COVID-19 outbreaks in Ontario LTC homes reported that lagged staff infection was a significant predictor of future resident deaths. 34 Screening protocols may be missing infected staff who are asymptomatic or minimally symptomatic, and low wages and scarce sick benefits mean that others may be working while ill. 6,8,36 Many staff are also employed part time and work at multi-ple health care facilities, something that has been linked to SARS-CoV-2 transmission among LTC facilities. 5,37 Our additional observation associating the number of active residents in an LTC home and the risk of an outbreak may be related to the fact that larger homes require more staff, thereby increasing the number of potential vectors for infection.…”
Section: Discussionmentioning
confidence: 99%
“…35 An earlier study of COVID-19 outbreaks in Ontario LTC homes reported that lagged staff infection was a significant predictor of future resident deaths. 34 Screening protocols may be missing infected staff who are asymptomatic or minimally symptomatic, and low wages and scarce sick benefits mean that others may be working while ill. 6,8,36 Many staff are also employed part time and work at multi-ple health care facilities, something that has been linked to SARS-CoV-2 transmission among LTC facilities. 5,37 Our additional observation associating the number of active residents in an LTC home and the risk of an outbreak may be related to the fact that larger homes require more staff, thereby increasing the number of potential vectors for infection.…”
Section: Discussionmentioning
confidence: 99%
“…The current global public health crisis caused by the COVID-19 pandemic has highlighted, among many other things, the critical importance of protecting vulnerable populations from infectious disease. Initial data from the COVID-19 outbreaks in the UK, China, and Italy have shown a significantly increased mortality rate for individuals 60 years of age and above regardless of the presence of comorbid conditions, highlighting the vulnerability of this segment of the population [1][2][3][4]. Older adults living in long-term care facilities are especially vulnerable as nosocomial transmission of COVID-19 has been observed in numerous facilities and has contributed to severe outbreaks in healthcare facilities [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has intensified these issues and paradoxically, reduced the face-to-face support they would normally receive from external healthcare providers (British Geriatrics Society, 2020a). The global pandemic has raised awareness of the important, skilled work carried out by care home staff and care homes' role within health and social care systems (Oliver, 2020a;Pollock et al, 2020). Our work has identified how few opportunities there are for the sector to identify priorities for research and comment on the relevance of guidance for the longterm care setting.…”
Section: Discussionmentioning
confidence: 99%